Harry Potter and the Order of the Phoenix - Rowling, J.K. (New York : Scholastic, 2003)
Juvenile fiction.
Sequel to: Harry Potter and the goblet of fire
Keywords: England -- Juvenile fiction; Hogwarts school of witchcraft and wizardry (Imaginary place) -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction